2021
DOI: 10.1007/s10151-020-02404-5
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of COVID-19 on surgical training: a systematic review

Abstract: Background Coronavirus disease has caused global disruption to health care. Non-urgent elective surgical cases have been cancelled, outpatient clinics have reduced and there has been a reduction in the number of patients presenting as an emergency. These factors will drastically affect the training opportunities of surgical trainees. The aim of this systematic review is to describe the impact of COVID-19 on surgical training globally. Methods The review was performed in line with Preferred Reporting Items for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
90
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 47 publications
5
90
0
8
Order By: Relevance
“…Despite the potential introduction of bias, the ‘unanimous’ results from all the surveys strengthen the findings [ 19 , 21 – 29 ]. Also, in agreement is the demonstrated reduction of performed cases on the electronic logbook of trainees [ 63 ], which provides an ‘independent’ confirmation of the effect demonstrated in the surveys.…”
Section: An Overviewsupporting
confidence: 56%
See 4 more Smart Citations
“…Despite the potential introduction of bias, the ‘unanimous’ results from all the surveys strengthen the findings [ 19 , 21 – 29 ]. Also, in agreement is the demonstrated reduction of performed cases on the electronic logbook of trainees [ 63 ], which provides an ‘independent’ confirmation of the effect demonstrated in the surveys.…”
Section: An Overviewsupporting
confidence: 56%
“…A great number of studies have reported a detrimental effect on surgical training. The majority of them described it ‘severe’ or ‘significant’ and some even ‘catastrophic’ [ 19 , 21 , 22 , 28 , 30 43 ]. These reports come both from developed [ 13 , 21 , 22 , 24 , 26 , 31 34 , 44 52 ] and developing countries [ 28 , 30 , 35 , 53 55 ] with very different healthcare systems.…”
Section: An Overviewmentioning
confidence: 99%
See 3 more Smart Citations